2014
DOI: 10.2190/ec.50.1.a
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Competence and Autonomy in Computer-Based Instruction Using a Skill-Challenge Balancing Strategy

Abstract: The present study aims to show if a skill-challenge balancing (SCB) instruction strategy can assist learners to motivationally engage in computer-based learning. Csikszentmihalyi's flow theory (self-control, curiosity, focus of attention, and intrinsic interest) was applied to an account of the optimal learning experience in SCB-based learning activities. Two empirical studies were carried out, where a group of learners were taught "Computer Networks" as part of a statutory curriculum at a tertiary institution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, interest, which can be described as a motivational state resulting from attraction to a certain domain or activity ( Reeve, 2008 ), was found to be related to flow (e.g., Eisenberger et al, 2005 ; Bressler and Bodzin, 2013 ; Bachen et al, 2016 ; Bricteux et al, 2017 ). Intrinsic motivation was investigated particularly often in its relation to flow, with evidence for a positive link found in various settings, such as education ( Schüler et al, 2010 ; Keller et al, 2011b ; Valenzuela and Codina, 2014 ; Meyer et al, 2016 ), Information and Communication Technologies (ICT) use ( Voiskounsky and Smyslova, 2003 ; Montgomery et al, 2004 ; Keller and Bless, 2008 ; Yan and Davison, 2013 ; Kim et al, 2014 ; Chen and Lu, 2016 ); daily activities ( Gaggioli et al, 2013 ) and physiological aspects ( Keller et al, 2011a ; Ulrich et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, interest, which can be described as a motivational state resulting from attraction to a certain domain or activity ( Reeve, 2008 ), was found to be related to flow (e.g., Eisenberger et al, 2005 ; Bressler and Bodzin, 2013 ; Bachen et al, 2016 ; Bricteux et al, 2017 ). Intrinsic motivation was investigated particularly often in its relation to flow, with evidence for a positive link found in various settings, such as education ( Schüler et al, 2010 ; Keller et al, 2011b ; Valenzuela and Codina, 2014 ; Meyer et al, 2016 ), Information and Communication Technologies (ICT) use ( Voiskounsky and Smyslova, 2003 ; Montgomery et al, 2004 ; Keller and Bless, 2008 ; Yan and Davison, 2013 ; Kim et al, 2014 ; Chen and Lu, 2016 ); daily activities ( Gaggioli et al, 2013 ) and physiological aspects ( Keller et al, 2011a ; Ulrich et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, raising children in a way that promotes self-determination will help them to engage in activities which will enhance their flow experience ( Schattke, 2011 ). In another study, it was found that flow enhanced learning motivation in computer-based learning systems if participants experienced self-control ( Kim et al, 2014 ). Goal-directed activities with clear instructions are supported in environments where the individual feels autonomous and self-determined (e.g., providing choices).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, raising children in a way that promotes self-determination will help them to engage in activities which will enhance their flow experience (Schattke, 2011). In another study, it was found that flow enhanced learning motivation in computer-based learning systems if participants experienced selfcontrol (Kim et al, 2014). Goal-directed activities with clear instructions are supported in environments where the individual feels autonomous and self-determined (e.g., providing choices).…”
Section: Self-determinationmentioning
confidence: 99%
“…Furthermore, interest, which can be described as a motivational state resulting from attraction to a certain domain or activity (Reeve, 2008), was found to be related to flow (e.g., Eisenberger et al, 2005;Bressler and Bodzin, 2013;Bachen et al, 2016;Bricteux et al, 2017). Intrinsic motivation was investigated particularly often in its relation to flow, with evidence for a positive link found in various settings, such as education (Schüler et al, 2010;Keller et al, 2011b;Valenzuela and Codina, 2014;Meyer et al, 2016), Information and Communication Technologies (ICT) use (Voiskounsky and Smyslova, 2003;Montgomery et al, 2004;Keller and Bless, 2008;Yan and Davison, 2013;Kim et al, 2014;Chen and Lu, 2016); daily activities (Gaggioli et al, 2013) and physiological aspects (Keller et al, 2011a;Ulrich et al, 2014).…”
Section: Motivational Indicatorsmentioning
confidence: 99%